Analysis of the Validity of Sparkol Videoscribe Media in Pancasila Education Learning in Grade IV of Elementary School - Rabbbani, Sukma; Reinita, Reinita (Journal of Educational Sciences, 2025)
Pancasila Education learning in elementary schools still faces obstacles in the form of low student enthusiasm due to the lack of use of interesting visual media. This condition causes students to be less motivated and find it difficult to understand the abstract values of Pancasila. This study aims to analyze the validity of Sparkol Videoscribe-based learning media on the material of Teamwork in My Neighborhood in grade IV of Elementary School. The research uses the Research and Development (R&D) method with the ADDIE development model. Validation was carried out by three expert validators, namely material experts, linguists, and media experts, through the Likert scale questionnaire instrument. The validation results showed that the material aspect obtained a score of 88%, the language aspect 96%, and the media aspect 97%, with an overall average of 93.70%, which is included in the "Highly Valid" category. These findings show that Sparkol Videoscribe media has met the technical content, language, and visual feasibility standards, so that it is suitable for use in the learning process of Pancasila Education in elementary schools.